Performance Improvement Based on Talent Management, Servant Leadership, Organizational Culture, and Organizational Commitment to HR Performance at Suzuya Rantauprapat Mall - Winda Widiastuti; Sumitro Sarkum; Siti Lam'ah Nasution (Quantitative Economics and Management Studies, 2023)
The purpose of this research is to analyze the effect of talent management, servant leadership, organizational culture on HR performance through organizational commitment. This research method is quantitative research, the population is all employees at the Suzuya Rantauprapat Mall. The sampling technique with purposive random sampling is a sampling technique that uses special criteria or considerations. The sample is 114 respondents. The research instrument was a questionnaire. Data analysis used multiple linear regression. The results of the study show that talent management has a positive and significant effect on HR Performance, Servant leadership has a positive and significant effect on HR Performance, Organizational Culture has a positive and significant effect on HR Performance, Organizational commitment has a positive and significant effect on HR performance. The implications of this research can be put forward theoretically and practically, there are efforts in order to improve the quality of HR performance to maintain and develop the organization in dealing with various company demands. With training using talent management principles for learning to increase talent. while the practical implication is that the results of this study are used as input for company owners to further improve the face of the company by replacing employees with quality ones. With training using the principles of talent management for learning to increase talent. while the practical implication is that the results of this study are used as input for company owners to further improve the face of the company by replacing employees with quality ones. With training using the principles of talent management for learning to increase talent. while the practical implication is that the results of this study are used as input for company owners to further improve the face of the company by replacing employees with quality ones.